ALCALDES ESPAÑOLES EN TWITTER: ¿DIÁLOGO O MONÓLOGO? - Pablo VÁZQUEZ SANDE (Fonseca, Journal of Communication, 2023)
The emergence of social networks allows that politicians, like any other citizen, can use them as a communication tool. In this research we want to see how is the contact established between the mayors of the Spanish provincial capitals and citizens. The aim is to determine if there is a genuine communicative intention and an orientation toward the interaction or if, instead of that, Spanish politicians use social networks just as a speaker of the messages that they transferred using other media, both online and offline.